PENGEMBANGAN MEDIA FLAT SHAPE BERBASIS LECTORA INSPIRE DALAM PEMBELAJARAN BANGUN DATAR PADA PESERTA DIDIK KELAS 2 SEKOLAH DASAR - Eka Nabilah Syahru Ramadhani; Kunti Dian Ayu Afiani; Ishmatun Naila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the validity, practicality and effectiveness of Flat Shape media based on Lectora Inspire in teaching mathematics about flat shapes in class 2 of elementary school. This research uses a development method with the ADDIE development model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SDIT Ar-Rayyan Surabaya, with 28 grade 2 students as research subjects. The data collection techniques used were questionnaires and tests. The research instruments include validation sheets, response questionnaires from teachers and students, and learning outcomes test sheets. The data analysis technique used is to evaluate the validity, effectiveness and practicality of flat shape media based on Lectora Inspire. The results of this research show that: (1) This media achieved a very high level of validity, with a percentage of 87% for media validation and 85% for material validation; (2) The practicality of flat shape media is rated very high based on positive responses from teachers (100%) and students (94%); (3) This media is effective in increasing students' learning completeness, with a percentage of 96% of one class reaching or exceeding the minimum completeness standard. Based on this research, it can be concluded that the Lectora Inspire-based flat shape media developed is very suitable for use as a learning tool for flat shape material in elementary schools. Keywords: flat build learning, flat shape media, lectora inspire